Interior Architecture and Gendered Space of the Apostle Islands Light Stations - Felty, Emma (My University, 2014)
The Apostle Islands are a chain of 22 islands that make up an archipelago in Lake Superior, off the Bayfield Peninsula in northern Wisconsin. These islands are unique for many reasons. They are exceptional examples of geological formations, have an abundance of wildlife and mining resources, and a long, detailed history. The Apostle Islands are home to the United States' highest concentration of lighthouses in one geographic area. Five islands are home to these light stations, which were established in the mid-19th century with the flourishing trade in iron, timber, and other resources, which made shipping aids along Superior's shores necessary. Lighthouses function as a family dwelling and government property simultaneously, which is an important intersection during the rise of domesticity in America. While women could control their domestic spheres on the mainland, lighthouse wives were under the influence of the lighthouse inspectors and had to shape their family lives to the US Light Service's regulations.
Keywords: Lighthouses--Wisconsin--Apostle Islands; Apostle Islands (Wis.)--History; Apostle Islands (Wis.)--Social life and customs